Living with vampires - Strong, Jeremy; Anderson, Scoular (Minneapolis, Minn. : Stone Arch Books, 2007)
In order to have an opportunity to spend time with the heavenly Miranda at a school dance, Kevin Vlad will have to let his vampire parents help chaperone, but how will he keep them from turning everyone into zombies?
2.2
5-8
Keywords: Parents -- Fiction; Schools -- Fiction; Vampires -- Fiction; Parents -- Fiction; School stories; Vampires -- Fiction